Becoming a new instructor a guide for college adjuncts and graduate students - Falk, Erika (New York Routledge, 2012)
"Becoming a New Instructor guides new instructors through the planning, preparation, and execution of their first class, whether it is in person or online. Like any good mentor, this book provides clear, simple instructions and makes best-practice recommendations. Becoming a New Instructor provides a step-by-step guide to writing a syllabus, a simple explanation for how to calculate grades, and many additional suggestions from an experienced teacher about how to run a class. Chronologically arranged from conceptualizing the class through putting together the syllabus, planning in-class time, running the class, and assigning grades, this book will answer any new instructors questions. Adjuncts and graduate students charged with teaching a college course will find this succinct guide invaluable. Special Features Include:An entire chapter on teaching online, plus "Concerns Specific to Online Instructors" throughout that connect chapter content to online teaching and CMS platformsExamples of best practice, checklists, sample assignments, syllabi, and rubrics that guide readers in creating materials for their own coursesGuidance specific to the needs of adjuncts and graduate students teaching a course for the first time"--Provided by publisher.
Includes bibliographical references and index.
Keywords: College teaching -- United States; College teachers, Part-time -- United States; Universities and colleges -- United States -- Faculty; First year teachers -- United States; Education, Higher -- United States